Accuracy of Neck stiffness, Kernig, Brudzinski, and Jolt Accentuation of Headache Signs in Early Detection of Meningitis - Alireza Ala; Farzad Rahmani; Sima Abdollahi; Zahra Parsian (Archives of Academic Emergency Medicine, 2018)
Introduction: The diagnostic value of clinical signs in early diagnosis of meningitis has been evaluated but the existing results are contradicting. The present study aimed to evaluate the accuracy of Kernig, Brudzinski, neck stiffness, and Jolt Accentuation of Headache (JAH) signs in this regard. Methods: In this diagnostic accuracy study, patients with suspected meningitis who were referred to the emergency department were examined regarding presence or absence of the mentioned clinical signs and screening performance characteristics of the signs were calculated. Cerebrospinal fluid analysis was used as the reference test. Results: 120 cases with mean age of 48.79 ± 21.68 years (18 – 93) were studied (63.3% male). Diagnosis of meningitis was confirmed for 45 (37.5%) cases. Neck stiffness (p < 0.001), Kernig (p < 0.001), Brudzinski (p < 0.001), and JAH (p < 0.001) had significantly higher frequency among patients with meningitis. The accuracy of neck stiffness, Kernig, Brudzinski, and JAH signs in early detection of meningitis were 0.676 (95% CI: 0.575-0.776), 0.667 (95% CI: 0.552-0.782), 0.720 (95% CI: 0.619-0.821), 0.749 (95% CI: 0.659-839), respectively. Conclusions: It seems that diagnostic value of JAH is higher than other clinical signs but the accuracy of all signs is in poor to fair range. JAH had the highest sensitivity and Kernig and Brudzinski had the highest specificity.